2023
DOI: 10.1038/s41591-022-02190-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient in vivo genome editing prevents hypertrophic cardiomyopathy in mice

Abstract: Dominant missense pathogenic variants in cardiac myosin heavy chain cause hypertrophic cardiomyopathy (HCM), a currently incurable disorder that increases risk for stroke, heart failure and sudden cardiac death. In this study, we assessed two different genetic therapies—an adenine base editor (ABE8e) and a potent Cas9 nuclease delivered by AAV9—to prevent disease in mice carrying the heterozygous HCM pathogenic variant myosin R403Q. One dose of dual-AAV9 vectors, each carrying one half of RNA-guided ABE8e, cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 55 publications
0
50
0
Order By: Relevance
“…The same AAVs were less efficient (<10%) in the postnatal heart in our hands. 22 With the development of base editing techniques, Myh6 recently was edited efficiently by ABE8e-NG at the Myh6 R403Q target site 23 and by ABEmax-NG at the humanized R403Q target site. 24 Previous studies focused on evaluating the efficacy and improving the base editing efficiency of a determined sequence variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same AAVs were less efficient (<10%) in the postnatal heart in our hands. 22 With the development of base editing techniques, Myh6 recently was edited efficiently by ABE8e-NG at the Myh6 R403Q target site 23 and by ABEmax-NG at the humanized R403Q target site. 24 Previous studies focused on evaluating the efficacy and improving the base editing efficiency of a determined sequence variant.…”
Section: Discussionmentioning
confidence: 99%
“…19 Delivery of base editors by viruses or nanoparticles has achieved therapeutic levels of editing in several animal models, including mouse and nonhuman primate models. 20,21 Our group 22 and others 23,24 previously used ABEs to correct a Myh6 PV in the hypertrophic mouse heart, highlighting the great potential of base editing to treat diseases.…”
mentioning
confidence: 99%
“…To enhance the current understanding of HCM, there are potential research areas that could be explored, including investigation of the genetic basis of HCM and the contribution of various genetic mutations to its development and progression [33,34]. This research could involve examining the effects of mutations in genes that encode proteins associated with cardiac muscle contraction, as well as genes that regulate cell growth and division in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Gene editing strategies have recently been shown to efficaciously convert pathogenic variants of MYH7 and MYH6 to nonpathogenic alleles in mouse models of HCM. 68,69 Chai et al 68 reported the use of different base editing strategies and showed their efficacy in correcting pathological phenotypes of HCM in patient-derived cells. Moreover, they applied the base editing to humanized mouse models containing the MYH7 p.R403Q pathogenic missense variant and showed that its postnatal correction might prevent the onset of the HCM phenotype.…”
Section: Hypertrophic Heart Disease In Adultsmentioning
confidence: 99%